Weighing The Options: The Unseen Companion in LAMOST J2354 is Likely a Massive White Dwarf - Michael A Tucker; Adam J. Wheeler; Dominick M. Rowan; Mark E. Huber (The Open Journal of Astrophysics, 2025)
LAMOST J235456.73+335625 (J2354) is a binary system hosting a $\sim 0.7~\rm M_\odot$ K dwarf and a $\sim 1.4~\rm M_\odot$ dark companion, supposedly a neutron star, in a 0.48d orbit. Here we present high- and low-resolution spectroscopy to better constrain the properties of the system. The low-resolution spectrum confirms that the luminous star is a slightly metal-poor K dwarf and strengthens the limits on any optical flux from the dimmer companion. We use the high-resolution spectra to measure atmospheric parameters ($T_{\rm eff}$, $\log g$, [Fe/H], $v_{\rm rot}\sin i$) and abundances for 8 elements for the K dwarf. We refine the mass of the compact object to $M_{\rm co} \sim 1.3~\rm M_\odot$ with a minimum mass of $M_{\rm co, min} = 1.23±0.04~\rm M_\odot$. The expected overabundance of intermediate-mass elements from the incident supernova ejecta is not detected in the K-dwarf atmosphere. This contrasts with known binaries hosting neutron stars where almost all companions show evidence for polluting material. Moving the neutron-star progenitor further from the K-dwarf at the time of explosion to minimize atmospheric pollution requires a finely-tuned kick to produce the current orbital separation of $\sim 3.3~\rm R_\odot$. Instead, we find that a massive white dwarf with a cooling age of $\gtrsim 3~$Gyr satisfies all observational constraints. The system likely experienced two common-envelope phases leading to its current state because the white dwarf progenitor was massive enough to ignite He-shell burning. The system will become a cataclysmic variable in the distant future when the K-dwarf evolves off of the main sequence. These short-period high-$q$ binaries represent an intriguing formation pathway for compact double white dwarf binaries and thermonuclear supernovae. An ultraviolet spectrum is the most promising avenue for directly detecting the white dwarf companion.